Simple statistical methods for software engineering : data and patterns - Pandian, C. Ravindranath; Kumar, Murali (Auerbach, 2015)
Sharing valuable insights into software engineering problems and solutions, the book not only explains the required statistical methods, but also offers many examples, review questions, and case studies that provide the understanding required to apply those methods to real-world problems. --